Single-cell RNA sequencing in studies of type 1 diabetes mellitus: modern state-of-the-art and technical peculiarities - Abdullatypov, Azat Vadimovich; Glushkova, Olga Valentinovna; Petriaikina, Ekaterina Sergeevna; Bogdanov, Viktor Pavlovich; Tabakov, Dmitry Vyacheslavovich; Akimov, Vasilii Eduardovich; Yudin, Vladimir Sergeevich; Keskinov, Anton Arturovich; Yudin, Sergey Mikhailovich; Volchkov, Pavel Yuryevich; Svetlichnyy, Dmitry Vladimirovich; Woroncow, Mary; et al. (Frontiers in Endocrinology, 2025)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease leading to destruction of pancreatic β-cells and loss of insulin production ability. Pathogenesis of T1DM is a complex process involving different types of immune cells, particularly, T-lymphocytes (including effector cells, Thelpers, regulatory lymphocytes, MAIT cells), B-lymphocytes, natural killers, monocytes, dendritic cells, and other minor cellular populations that form autoimmune response against islet cells. The heterogeneity of intercellular communications in the pancreas and adjacent lymph nodes of patients, as well as diverse functional state of islet cells, make a significant contribution to the pathogenesis of this disease. This makes the detailed consideration of immune cell subpopulations very essential for investigating the pathogenesis of the disease. Understanding the relations between changes of transcriptional activities in different cellular subtypes may allow to study the pathogenetic mechanism of T1DM in more detail, which could further be applied in both diagnostics and treatment. Single-cell RNA sequencing (scRNA-seq) allows to examine the interactions between immune cell subtypes and to identify differentially expressed genes specific for early stages of T1DM in particular cell subtypes. This review summarizes modern studies focusing on application of scRNA-seq for the studies of T1DM pathogenesis, novel biomarkers of manifestation, progression, and treatment efficiency for diabetes and its complications. The review covers studies on different cells and human tissues (endocrine, exocrine and immune pancreatic cells, PBMC) and model animals with experimental T1DM and its complications.